Publication of clinical trials on medicinal products: follow-up on trials authorized in Hungary - Kinga Amália Sándor-Bajusz; Andrea Kraut; Odgerel Baasan; Gergely Márovics; Károly Berényi; Szimonetta Lohner (Trials, 2022)
Abstract Background Clinical research should provide reliable evidence to clinicians, health policy makers, and researchers. The reliability of evidence will be assured once study planning, conducting, and reporting of results are transparent. The present research investigates publication rates, time until publication, and characteristics of clinical trials on medicinal products associated with timely publication of results, measures of scientific impact, authorship, and open access publication. Methods Clinical trials authorized in Hungary in 2012 were followed until publication and/or June 2020. Corresponding scientific publications were searched via clinical trial registries, PubMed (MEDLINE), and Google. Results Overall, 330 clinical trials were authorized in 2012 of which 232 trials were completed for more than 1 year in June 2020. The proportion of industry initiation was high (97%). Time to publication was 21 (22) months [median (IQR)]. Time to publication was significantly shorter when trials involved both European and non-European countries (26 vs 69 months [median]; hazard ratio = 0.38, 95% CI 0.22–0.66, p< 0.001), and were registered in both EU CTR and clinicaltrials.gov (27 vs 88 months; hazard ratio = 0.24, 95% CI 0.11–0.54; p< 0.001) based on survival analyses. A significant amount (24.1%) of unpublished clinical trial results were accessible in a trial register. The majority of available publications were published “open access” (70.93%). A minority of identified publications had a Hungarian author (21.5%). Conclusions We encourage academic researchers to plan, register and conduct trials on medicinal products. Registries should be considered as an important source of information of clinical trial results. Publications with domestic co-authors contribute to the research output of a country. Measurable domestic scientific impact of trials on medicinal products needs further improvement.